Compulsory Education Phenomenon for Islamic Education in Indonesia - Gunawan, Gunawan; Simanjuntak, Muhammad Adyan; Marisa, Siti (Al'Adzkiya Journal, 2022)
The education level in Indonesia aims to create a society that has the lowest education, namely SMA/Equivalent, so that scientific competence, learning experience and thinking patterns have knowledge in general, so that in the process of interacting in the world of work, this is also the target of religious education institutions. which are non-formal in nature such as al-Quran memorizing schools (tahfiz schools), the method in this study uses the literature study method, namely discussing literature both from laws and regulations, government regulations, related ministerial regulations and education regulations. Basically Compulsory Education/compulsory education is a government program that has been running in Indonesia, namely the 9-year and 12-year compulsory education program, this program is running until now.Compulsory Education, Compulsory Islamic Education